Prediction of Financial Health of Selected Yes Banks Ltd Using X-Score Model - Arshe AZAM (PT Keberlanjutan Strategis Indonesia, 2025)
In recent years, banks have increasingly encountered significant challenges, particularly related to financial irregularities, mismanagement, and fraud. This study aims to evaluate the economic health and financial performance of Yes Bank Ltd. over a ten-year period, from 2013–14 to 2022–23. The analysis is based on secondary data obtained from Capitaline and is conducted using Microsoft Excel and SPSS software. To assess the financial condition of the bank, the study applies the X-score model alongside simple linear regression techniques. The results reveal that while Yes Bank Ltd. remained financially stable during the majority of the observed years, it experienced financial distress in certain periods, which notably influenced the X-score outcomes. These fluctuations highlight vulnerabilities in the bank's financial structure during those years. It is important to note that the study is limited to one bank and a single predictive model. Therefore, future research is encouraged to expand the analysis by including multiple banks or industries and incorporating a variety of predictive tools and models to obtain more generalizable and robust insights.